Nacre-mimetic composite with intrinsic self-healing and shape-programming capability - Gaolai Du (Nature Portfolio, 2019)
Incorporation of self-healing and shape programming capabilities into rigid, structural composite is highly desirable yet challenging. Here, the authors report a nacre-mimetic composite obtained by infiltrating a switchable Diels-Alder network polymer into a scaffold of alumina capable of self-healing internal damage.